Neuromuscular responses to two whole-body vibration modalities during dynamic squats - Amonette, W. E.; Abercromby, A. F. J.; Hinman, M.; Paloski, W. H.
The data show a significant (p<0.05) multivariate VB and VB x M interaction effect. Follow-up tests showed EMG activity of the GS (d=.431), VL (.286), and TA (.415) but not BF were significantly greater (p<0.05) during RV vibration compared to BL. VV increased EMGrms above BL in GS (d=.341), VL (.238), and TA (.604) but not BF. CONCLUSION: These data suggest that WBV enhances muscle activation in the lower- and upper-leg during dynamic squats. RV elicits a greater response in the GS while VV elicits larger responses in the TA, possibly due to the effects of anteroposterior VV platform instability. PRACTICAL APPLICATION: WBV may enhance responses to lower-body strength training, possibly through the mechanism of increased motoneuron activation.